2015
DOI: 10.1155/2015/276753
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Tribological Properties and Lubrication Mechanism of Graphite Nanoparticles as Vegetable Based Oil Additive

Abstract: This paper used graphite nanoparticles with the diameter of 35 and 80 nm and LB2000 vegetable based oil to prepare graphite oil-based nanofluids with different volume fractions by two-step method. The tribological properties of graphite nanoparticles as LB2000 vegetable based oil additive were investigated with a pin-on-disk friction and wear tester. Field emission scanning electron microscope (FE-SEM) and energy dispersive spectroscopy (EDS) were used to examine the morphology and the content of some typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
0
34
1
Order By: Relevance
“…In the same vein, the tribological parameters in our research work are much better than those of Anand et al [61] who used phosphonium ionic liquid additives in diesel engine lubricants. More to the point, the experimental predictions in our research effort on wear and friction minimization are even far superior to the findings of Chen et al [62] and Su et al [63] who used nano-additives in different lubricating media. With an advantage, the calculated values of mass and volume losses of the aluminum pin show that polytron additive attenuates the mass wear rate by an order of magnitude while the volume wear rate of aluminum is alleviated by two orders of magnitude and these outcomes in sequence yield just a nominal value for the wear coefficient as can be noticed from Table 8.…”
Section: Resultscontrasting
confidence: 74%
“…In the same vein, the tribological parameters in our research work are much better than those of Anand et al [61] who used phosphonium ionic liquid additives in diesel engine lubricants. More to the point, the experimental predictions in our research effort on wear and friction minimization are even far superior to the findings of Chen et al [62] and Su et al [63] who used nano-additives in different lubricating media. With an advantage, the calculated values of mass and volume losses of the aluminum pin show that polytron additive attenuates the mass wear rate by an order of magnitude while the volume wear rate of aluminum is alleviated by two orders of magnitude and these outcomes in sequence yield just a nominal value for the wear coefficient as can be noticed from Table 8.…”
Section: Resultscontrasting
confidence: 74%
“…Hu substances to produce a lubricating film that reduces the surface friction and wear. Su et al [105] observed the lubricating wear scar surface of 0.25% graphite nanoparticles added to plant-based oil. Graphite nanoparticles can be stably adsorbed on friction surface, which forms a physical adsorption film on a friction surface.…”
Section: Film Formation Mechanismmentioning
confidence: 99%
“…Nanomaterials can fill a concave area on a friction surface to smoothen it. Su et al [105] developed a model for simulating the self-healing mechanisms of nanomaterials (Fig. 6).…”
Section: Self-healing Mechanismmentioning
confidence: 99%
“…Minh et al, [20] claimed that Al2O3 nanoparticles produced excellent tribological and anti-toxic properties. While Su et al, [34] mentioned that graphite nanoparticles were able to reduce anti-friction characteristics where a physical deposition layer could form on the surface thereby resulting in low friction forces. Sayuti et al, [35] revealed that the Vickers hardness of silicon dioxide (SiO2) nanoparticle is 1000kgfmm-2 which possesses good mechanical properties of hard and brittle particles.…”
Section: Nanomaterialsmentioning
confidence: 99%